The Importance of Neglect in Policy-Making - Vries, Michiel S. De. author. aut Link
XVII, 203 p.
Keywords: De Vries argues that it is possible to explain when and in what direction policy change is likely to occur. He argues that what is neglected at present is likely to become dominant in policies of the near future. With the birth of a new policy generation a convergence towards meeting the dominant value of that generation will become evident.